Stabilization of the hindered urea bond through de-tert-butylation. Issue 31 (19th March 2021) - Yang, Yingfeng; Ying, Hanze; Jia, Yunchao; Chen, Yingying; Cheng, Jianjun
Abstract : A facile acid-assisted de- tert -butylation reaction that can instantly "turn off" the dynamicity of hindered urea bonds (HUBs) and stabilize HUB-containing structures. Abstract : We report the discovery of an acid-assisted de- tert -butylation reaction that can instantly "turn off" the dynamicity of hindered urea bonds (HUBs) and thus broaden their applications. The reaction is demonstrated to be widely applicable to different hindered urea substrates, leading to improved chemical stabilities and mechanical properties of HUB-containing materials.